Inequality of Educational Opportunity : The Relationship between Access, Affordability, and Quality of Private Schools in Lagos, Nigeria - Baum, Donald R.; Abdul-Hamid, Husein; Wesley, Hugo T. (Taylor and Francis, 2018)
Using data from a census of private schools in one of Lagos, Nigeria’s administrative jurisdictions, this paper explores the linkages between a heterogeneous sector of private schools and issues of school access, affordability, quality, and ultimately social mobility for households at the bottom of the income distribution. Although a large private education market has buoyed Lagos’s growth towards near-universal primary enrolment, this heterogeneous school sector appears to be providing socially stratifying paths towards educational attainment. We apply Lucas’s theory of effectively maintained inequality to assess the extent to which access to higher quality education services within the private sector is determined by cost. We find that higher-cost private schools provide students with greater opportunities to study in institutions with higher quality inputs and increased potential for progression within the educational system. As such, it is highly likely that these schools are primarily accessible to students at the upper ends of the income distribution.